Identification determination of potentially toxic elements in water and sediments from blood and Mokolo rivers in Limpopo Province, South Africa - Matabane, Dithobolong Lovia (My University, 2019)
The increase in industrialisation such as mining and smelting activities is among the main sources of heavy metal pollution in the environment. These potentially toxic elements may be adsorbed directly by sediments of water course and may affect the inhabiting flora and fauna. Potentially toxic elements are not permanently fixed by the sediments since changes in environmental conditions can mobilise these elements from sediments to water. Thus, analysis of sediments could indicate the degree of environmental contamination by potentially toxic elements and therefore are suitable for pollution studies. The aim of this study was to assess and quantify the levels of selected potentially toxic elements (Mn, Zn, Ni, Cu, Cr, Pb, V, Cd, As, Se and Fe) in sediments and water samples collected from Blood and Mokolo Rivers in Limpopo Province, South Africa. Water and sediments samples were collected from 10 sampling sites from each river. Water samples were filtered and acidified with HNO3 prior to analysis for preservation of elements. Potentially toxic elements in water samples were analysed by ICP-MS and the results validated by analysing standard reference material of water (SRM 1634f). Concentration levels of potentially toxic elements in samples from the water of Mokolo and Blood Rivers during low and high flow seasons were determined with ICP-MS. The levels in the water of Mokolo and Blood Rivers followed the order of Mn > Se > Zn > Cr > Pb > V > Cu > As > Ni > Cd > Fe in Mokolo River and Mn > Se > Zn > Cr > V > Ni > Cu > As > Pb > Cd > Fe during high flow season, Mn > Se > Zn > Cr > Cu > V > As > Pb > Ni > Cd > Fe and Mn > Zn > Se > Cr > V > Ni > Cu > As > Pb > Cd >Fe during low flow season, respectively. As expected, the concentrations of selected elements determined during the low flow season exceeded the high flow season for both rivers, which confirms acceptability of the analytical method performance. The analysis of variance (ANOVA) showed significant differences (P<0.05) in the concentrations of the elements seasonally. The concentrations of the toxic metals in the water samples of Mokolo and Blood Rivers were below the maximum permissible levels (MPLs) set by different organisations such as World Health Organisation (WHO) and Department of Water and Sanitation (DWS). Comparison of concentrations of elements in sediments determined during high flow and low flow seasons was done to establish the variation on the levels of the elements between seasons. Levels of potentially toxic elements in sediments of Mokolo and Blood Rivers followed the order Fe > Cr > Mn > V > Zn > As > Ni > Cu > Pb > Cd > Se and Fe > Mn > Cr > Ni> V > Zn> Cu > Pb > As > Cd> Se during high flow season as well as Fe > Mn > Cr > V > Zn > Ni > Pb > Cu > As > Cd > Se and Fe > Mn > Cr > Zn > V > Ni > Cu > Pb > As > Cd > Se during low flow season, respectively. The ANOVA results showed significant differences in the concentrations of the elements between two seasons and that concentrations of the elements determined in sediments during low flow season were significantly higher than the high flow season levels. Compared with sediments quality guidelines (SQGs), the concentrations of Fe, Mn, Ni and Cr in the sediments of Mokolo and Blood Rivers were above the SQGs, which could pose the risk to sediments dwelling organisms. The Community Bureau of Reference (BCR) sequential extraction method was applied to extract selected potentially toxic elements (Cd, Cr, Cu, Fe, Ni, Pb and Zn) in sediments samples. Microwave-assisted sequential extraction procedure was developed and employed for extraction of the selected potentially toxic elements in sediments samples. This method enables safe and fast extraction of potentially toxic elements in sediments using smaller volume of reagents. The methods employed were validated with the BCR-701 certified reference material of sediments. The Efficiency and reliability of the microwave-assisted sequential extraction method was shown by calculating the percent recoveries. The percent recoveries were within acceptable range for method validation. Following the sequential extraction analysis, the risk assessment study was done to determine the effect of the potentially toxic elements in the sediments to the water quality. The calculated individual contamination factor (ICF), global contamination factor (GCF) and risk assessment code (RAC) values of Cd, Cu, Ni and Pb indicated that the elements were mobile and may be bioavailable in the aquatic environment. vii The assessment of eco-toxicological risk indicated that the elements in sediments samples collected from Blood River are at high toxicity risk level and thus, could pose threat to sediments dwelling organisms and humans through consumption of crops irrigated with the river water.
Thesis (M. Sc. (Chemistry)) -- University of Limpopo, 2019
Keywords: Metallurgy; Toxic elements in water; Sediments from blood and Mokolo river; Industrialization - Developing countries; Mines and mining; Metallurgy; Contaminated sediments